Religious culture reflection of young Muslims community - Guntoro Guntoro; Noorhaidi Hasan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2023)
The identity formation of young Muslims is a complex issue influenced by various factors such as transition, culture, religion, and external factors like parents and environment. Despite facing challenges, young Muslims have the power to adapt, select, and appropriate their cultural identity in the contemporary Islamic era. This study aims to describe the reflection of religious life through three dimensions: belief, worship, and social society. The young Muslim ACM (Ayo Cinta Masjid) community has various social activities and strong religious culture. Through these practices, the ACM community strives to build and apply the practice of religiosity as a fancy religious life identity while maintaining the basic values and Islamic principles. The construction of ACM community religiosity identity begins with various religious activities such as congregational prayers, great recitation (tablīgh akbar), ACM riders subuhan, sharing time weekends, ACM volunteers, prepekan, and other activities. In the worship dimension, the religiosity of the ACM community can be identified from the intensity and the practice of worship in daily life through various religious activities. Meanwhile, in the social dimension, the religiosity of the ACM community is reflected in social life by carrying out positive and constructive activities for others based on religious awareness.